2010
DOI: 10.1002/srin.201000089
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Support Rollers of Continuous Casting Machines on Heat Transfer and on Stress‐Strain of Slabs in Secondary Cooling

Abstract: The processes of solidification and heat extraction are important for the continuous casting of steel. In this work, investigations on the influence of support roller contact on solidification in a strand of a slab caster, such as surface temperature and strand shell growth, and on thermal strain and stress in the slab have been carried out. The results show that roller contact has an influence on the solidification of steel and on the thermomechanical behaviour of the strand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“….......................... (12) Where, N R i is the roller number of i th cooling zone; R i L is the contact length between roller and slab in i th cooling zone, m; Z i L is the length of the i th cooling zone, m. According to the previous research, 17,20,21) h c i is set as 0.4-1.4 Kw/(m 2 ·°C), and R i L is equal to 0.02 m. According to the experimental results of F. Ramstorfer et al 6) and Nozaki et al, 11) the h i w is the function of the water flux distribution, and it could be expressed as:…”
Section: Boundary Conditionsmentioning
confidence: 99%
“….......................... (12) Where, N R i is the roller number of i th cooling zone; R i L is the contact length between roller and slab in i th cooling zone, m; Z i L is the length of the i th cooling zone, m. According to the previous research, 17,20,21) h c i is set as 0.4-1.4 Kw/(m 2 ·°C), and R i L is equal to 0.02 m. According to the experimental results of F. Ramstorfer et al 6) and Nozaki et al, 11) the h i w is the function of the water flux distribution, and it could be expressed as:…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…At present, the researches of the influence on heat transfer between the roll and slab mainly focus on the contact angle, the variation of slab temperature, and the oxidation process of rolls under different conditions. Xia and Schiefermüller [2] pointed out that the contact length between the slab and roll has an important influence on the distribution of temperature and stress-strain of the roll in the secondary cooling zone and found that the maximum stress on the support roll under this experimental condition was less than 70 Mpa. Javurek et al [3] compared heat transfer models of rolls with different dimensions and proposed mathematical models with different complexities to calculate the temperature of the slab and roll.…”
Section: Introductionmentioning
confidence: 80%
“…Therefore, it is necessary to study the change of roll yield strength at high temperature to prolong the roll service life in the actual production process. Xia and Schiefermüller found that the maximum stress on the support roll was less than 70 MPa. Liu and Bayoumi et al studied the stress state of the roll during the soft reduction process in slab continuous casting and found that the stress of the roll was generally less than 50 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…For roll contact: hconti=hR/Si·NRi·LR/SLi where, h i cont is the equivalent heat transfer coefficient between the strand and rolls, W (m 2 °C) −1 ; N i R is the number of roll; h i R / S , L R / S , respectively, denote the heat transfer coefficient and the contact length between the strand and roll in W (m 2 °C) −1 and m. According to the previous work, h i R / S ranges from 1000 to 1300 and L R / S was set as 0.02; L i represents the total length of the i th cooling zone, m.…”
Section: Thermal‐mechanical Coupling Modelmentioning
confidence: 97%